Efficiency of The Functioning of The “Wholesale and Retail Trade” Industry in The European Union - Kalinkova, Sabrina (Research Papers, 2023)
The successful development of a national economy is predetermined to the highest degree by the efficiency with which its individual economic industries function. The object of the present research is “Wholesale and retail trade” industry for the economies of the state-members of the European Union, and the subject of research is the efficiency with which the industry functions in the period 2010 – 2020. The main goal of the research is to trace and outline the main trends in the development of the industry and their comparison with the basic economic statements for the trends in economies worldwide.
Keywords: Industrial development; Trade; Еfficiency; Input-output model